Party rules, party resources and the politics of parliamentary democracies: How parties organize in the 21st century. (November 2016) - Poguntke, Thomas; Scarrow, Susan E; Webb, Paul D; Allern, Elin H; Aylott, Nicholas; van Biezen, Ingrid; Calossi, Enrico; Lobo, Marina Costa; Cross, William P; Deschouwer, Kris; Enyedi, Zsolt; Fabre, Elodie; et al.
This article introduces the first findings of the Political Party Database Project, a major survey of party organizations in parliamentary and semi-presidential democracies. The project's first round of data covers 122 parties in 19 countries. In this article, we describe the scope of the database, then investigate what it tells us about contemporary party organization in these countries, focusing on parties' resources, structures and internal decision-making. We examine organizational patterns by country and party family, and where possible we make temporal comparisons with older data sets. Our analyses suggest a remarkable coexistence of uniformity and diversity. In terms of the major organizational resources on which parties can draw, such as members, staff and finance, the new evidence largely confirms the continuation of trends identified in previous research: that is, declining membership, but enhanced financial resources and more paid staff. We also find remarkable uniformity regarding the core architecture of party organizations. At the same time, however, we find substantial variation between countries and party families in terms of their internal processes, with particular regard to how internally democratic they are, and the forms that this democratization takes.